The Repair Shop as a Sign of the Cultural Resurgence of Craft and Manual Work - Hyland, Terry (Advances in Social Sciences Research Journal, 2021)
Given the low standing of vocational studies in English education and other systems around the world at the present time, it is refreshing to note the resurgence of interest in craft and manual work. The currently popular BBC programme, The Repair Shop, is a celebration of this renewed interest and offers an especially graphic representation of the virtues and values of craft and handwork. It is suggested that such example of cultural practice can help towards the enhancement of vocational education and training in schools and colleges, and assist in bridging of the divisions between academic and vocational studies at all levels of education systems.